A new large Bauriamorph from the Cynognathus-zone of South Africa - Brink, A. S. (Bernard Price Institute for Palaeontological Research, 1965)
The specimen forming the subject of this paper is the anterior two-thirds of a very large Bauria skull. It is described as a new species, Bauria robusta. It is pointed out that the skull is perhaps as much as 20 per cent larger than the largest known specimen of Bauria cynops, which in turn is about 15 per cent larger than the average of all other known specimens of the genotype. Many of the measurements are derived from reconstructed figures and if these measurements should prove to be less, the new skull would undoubtedly prove to be proportionally different, in which case its recognition as a new species would be more substantial. The features on which the specimen can at present be recognised as a new species are size, the greater number of cheek teeth (11 as compared with 9 in B. cynops), the weaker canines and the absence of an interpterygoid vacuity.
Main article
Keywords: Bauriamorph; Cynognathus-zone; Karoo; South Africa